Modern C quick syntax reference : a pocket guide to the language, APIs, and library - Olsson, Mikael (Web programmer) (Apress, 2019)
Discover how C's efficiency makes it a popular choice in a wide variety of applications and operating systems with special applicability to wearables, game programming, system level programming, embedded device/firmware programming and in Arduino and related electronics hobbies in this condensed code and syntax guide. This book presents the essential C syntax in a well-organized format that can be used as a quick and handy reference. In this book, you will find short, simple, and focused code examples; and a well laid out table of contents and a comprehensive index allowing easy review. You won't find any technical jargon, bloated samples, drawn out history lessons, or witty stories. What you will find is a language reference that is concise, to the point and highly accessible. The book is packed with useful information and is a must-have for any C programmer. You will: Code for some of today's modern and popular firmware and systems How to do embedded programming found in Arduino and related hardware boards Program microcontrollers for robots and boards Handle low-level programming and memory management Leverage operating systems such as Linux and Unix.